Penilaian Keputusan Akuisisi Kapal dan Analisis Dampak Dengan Pendekatan Metode Pairwise Comparison Dengan Kombinasi Lean Administration dan Benefit-Cost Analysis - kristiana, dian; D. Putranta , Dinariyana (Publikasi Indonesia, 2025)
Ship procurement for shipping companies is a strategic and costly decision that requires careful consideration. The limited availability of secondhand container ships meeting the criteria forces companies to adjust the quality of purchased ships. This study employs the Pairwise Comparison (PC), Benefit-Cost Analysis (CBA), and Lean Administration methods to evaluate ship criteria, financial impacts, and acquisition process efficiency. PC assesses ship selection criteria from various stakeholder perspectives, while Lean Administration analyzes the acquisition process using Value Stream Mapping (VSM). CBA includes NPV, IRR, BCR, ROI, and PP to measure investment feasibility. Results show that ships with superior specifications are the top priority (49%), followed by payload (31%) and price (20%). Fuel consumption is the dominant sub-criterion under ship specifications, with a weight of 42%. Acquisition process analysis reveals that only 45% of the time adds value, while the rest is wasted, inflating acquisition costs by up to 10% of the ship's price. Although all ships show positive investment indicators, some parameters fall short of expectations, reducing profit margins. The assessment of ship conditions does not always reflect their economic value or acquisition efficiency due to the complexity of interrelated factors. Structured planning involving multiple perspectives is key to improving decision-making quality amid complex and suboptimal conditions in ship procurement.